2021
DOI: 10.1149/1945-7111/abe8b7
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Quantification of Diclofenac Using a Modified CPE Enriched With TiO2Nanoparticles and MWCNT

Abstract: This work describes the development of a voltammetric methodology based on a carbon paste electrode enriched with multiwalled carbon nanotubes and TiO2 nanoparticles, for the electrochemical quantification of diclofenac. All stages of the methodology were optimized by a Box-Behnken experimental design. The electrochemical behavior of diclofenac was studied by cyclic voltammetry. Results showed that the oxidation of diclofenac is favored by the presence of both MWCNT and TiO2 nanostructures since a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…modify the surface of the electrode, however in a previous study by the authors 33 it was shown that, with the proposed electrode, there is no significant effect on the diclofenac signal. Finally, the values of the MSE were calculated using Eq.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…modify the surface of the electrode, however in a previous study by the authors 33 it was shown that, with the proposed electrode, there is no significant effect on the diclofenac signal. Finally, the values of the MSE were calculated using Eq.…”
Section: Discussionmentioning
confidence: 69%
“…Even when the interference effect of caffeine is not evident since its anodic peak appears at higher potentials than that of diclofenac (Fig. 1, 1.37 V), previous studies of the research group 33 demonstrated that caffeine adsorbs in the electrode's surface changing its characteristics and influencing the diclofenac response. This can be observed in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In recent decades, electrochemical sensors coupled with voltammetric techniques such as Cyclic Voltammetry (CV) and Differential Pulse Voltammetry (DPV), were the most widely used because they present interesting characteristics for the determination of NSAIDs, dopamine, uric acid, ascorbic acid, among others, such as high sensitivity, high selectivity and accuracy, as well as low cost, and shorter analysis time compared to mass spectroscopy and HPLC [ 7 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%